The Effectiveness of Language Games in Enhancing Arabic Language Skills: A Linguistic Study at Gontor Islamic Boarding School 8, Aceh: Efektivitas Permainan Bahasa dalam Meningkatkan Keterampilan Bahasa Arab: Sebuah Studi Linguistik di Pondok Pesantren Gontor 8 Aceh - Anshar Zulhelmi (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2025)
This study examines the effectiveness of language games in enhancing Arabic language skills at Gontor Islamic Boarding School 8 in Aceh. The research employs a procedural approach, where the researcher designs and implements language games directly in the classroom. Pre- and post-tests were administered to assess students' proficiency in Arabic, with data also collected through observations and student feedback. The results indicate a significant improvement in students' Arabic language skills, particularly in speaking and listening, after the intervention. The average pre-test score was 28.33, while the post-test score increased to 72.5, showing a marked improvement in academic performance. Observations revealed that students were more engaged and motivated during the lessons that incorporated language games, supporting the idea that these games stimulate student participation and enthusiasm for learning. This study highlights the positive impact of language games in increasing student engagement, enhancing motivation, and improving language acquisition outcomes. The findings suggest that language games are an effective tool for teaching Arabic and can be integrated into the curriculum to improve students' linguistic skills. Further research is recommended to explore the long-term effects and how different types of language games impact specific language learning areas. Penelitian ini mengkaji efektivitas permainan bahasa dalam meningkatkan keterampilan bahasa Arab di Pondok Pesantren Gontor 8 di Aceh. Penelitian ini menggunakan pendekatan prosedural, di mana peneliti merancang dan menerapkan permainan bahasa secara langsung di dalam kelas. Pre-test dan post-test dilakukan untuk menilai kemampuan siswa dalam bahasa Arab, dengan data juga dikumpulkan melalui observasi dan umpan balik dari siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam keterampilan bahasa Arab siswa, terutama dalam berbicara dan mendengarkan, setelah intervensi. Skor rata-rata pre-test adalah 28,33, sementara skor post-test meningkat menjadi 72,5, menunjukkan peningkatan yang jelas dalam kinerja akademik. Observasi mengungkapkan bahwa siswa lebih terlibat dan termotivasi selama pelajaran yang melibatkan permainan bahasa, mendukung ide bahwa permainan ini merangsang partisipasi siswa dan antusiasme dalam belajar. Penelitian ini menyoroti dampak positif permainan bahasa dalam meningkatkan keterlibatan siswa, meningkatkan motivasi, dan memperbaiki hasil perolehan bahasa. Temuan ini menunjukkan bahwa permainan bahasa adalah alat yang efektif untuk mengajar bahasa Arab dan dapat diintegrasikan ke dalam kurikulum untuk meningkatkan keterampilan bahasa siswa. Penelitian lebih lanjut disarankan untuk mengeksplorasi efek jangka panjang dan bagaimana berbagai jenis permainan bahasa mempengaruhi area pembelajaran bahasa tertentu